Purification and Characterization of the Recombinant Thermus sp. Strain T2 α-Galactosidase Expressed in Escherichia coli - Ishiguro, Mitsunori (American Society for Microbiology, 2001)
The nucleotide sequence of the Thermus sp. strain T2 DNA coding for a thermostable α-galactosidase was determined. The deduced amino acid sequence of the enzyme predicts a polypeptide of 474 amino acids (M(r), 53,514). The observed homology between the deduced amino acid sequences of the enzyme and α-galactosidase from Thermus brockianus was over 70%. Thermus sp. strain T2 α-galactosidase was expressed in its active form in Escherichia coli and purified. Native polyacrylamide gel electrophoresis and gel filtration chromatography data suggest that the enzyme is octameric. The enzyme was most active at 75°C for p-nitrophenyl-α-d-galactopyranoside hydrolysis, and it retained 50% of its initial activity after 1 h of incubation at 70°C. The enzyme was extremely stable over a broad range of pH (pH 6 to 13) after treatment at 40°C for 1 h. The enzyme acted on the terminal α-galactosyl residue, not on the side chain residue, of the galactomanno-oligosaccharides as well as those of yeasts and Mortierella vinacea α-galactosidase I. The enzyme has only one Cys residue in the molecule. para-Chloromercuribenzoic acid completely inhibited the enzyme but did not affect the mutant enzyme which contained Ala instead of Cys, indicating that this Cys residue is not responsible for its catalytic function.